The Effect of Motivation and Job Satisfaction on Performance Through Employee Engagement as a Mediating Variable - Untung Cristoper Simarmata; Rojuaniah (International Journal of Economics (IJEC), 2025)
Employee performance an important role in human resource strategy that can determine the success of a company in achieving its vision and mission. The purpose of this study was to measure more specifically the influence of work motivation, job satisfaction on employee engagement and the performance of permanent employees of PT. Federal International Finance. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire to 170 respondents of permanent employees of PT. Federal International Finance, male and female with a work period of more than 4 years with staff positions. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that work motivation and job satisfaction have a direct effect on employee engagement. Furthermore, work motivation and job satisfaction have a direct effect on employee performance. Next, employee engagement has a direct effect on employee performance. Then employee engagement is proven to be a mediation between the relationship between work motivation and job satisfaction on employee performance. This study contributes to the company in maintaining and improving employee performance to be able to motivate employees to increase their knowledge and maximize their potential in this company. Then the company can prioritize employees who have more skills and contributions to the company in providing compensation. For further research, the researcher suggests expanding the research area and looking for objects in other fields.